The Role of the Parental Treatment in Predicting the Subversive Behavior of Pre-School Children - Yonis, Hazah Salem; Almufti, Birivan Abdullah (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of preschool children's responses to both parental treatment styles and disruptive behavior and compare them with the hypothetical mean. It also seeks to examine the relationship between parental treatment styles and disruptive behavior, as well as predict disruptive behavior based on these styles. The descriptive correlational method was used to study the research variables. The sample of the study consists of 50 boys and girls with disruptive behavior disorder, was selected using simple random sampling, representing 75% of the study population. A scale for parental treatment styles and disruptive behavior in preschool children was developed. The results of the study showed a significant negative correlation between the democratic and encouraging parental treatment styles and disruptive behavior in preschool children, while a significant positive correlation was found between the authoritarian parental treatment style and disruptive behavior. There was no significant correlation between the encouraging parental treatment style and disruptive behavior. Additionally, an overall significant negative correlation was found between parental treatment styles and disruptive behavior in preschool children. The democratic and encouraging parental treatment styles had a negative and effective role in reducing disruptive behavior, while the authoritarian style had a positive influence on increasing disruptive behavior. Finally, no effective role was found for the tolerant style in influencing disruptive behavior. Based on these findings, the researchers provided several conclusions, recommendations, and suggestions.